2010
DOI: 10.3109/14992021003777267
|View full text |Cite
|
Sign up to set email alerts
|

Hearing aids as an adjunct to counseling: Tinnitus patients who choose amplification do better than those that don't

Abstract: Hearing aids are commonly used for tinnitus management ( Kochkin & Tyler, 2008 ) but there is limited evidence to support their use. The purpose of this study was to quantify the effectiveness of hearing aids and counseling as a tinnitus treatment option. This study is a retrospective analysis of tinnitus handicap questionnaire (THQ, Kuk et al, 1990 ) results from 58 tinnitus patients with hearing loss who received counseling, and (1) chose to follow recommendations of hearing aid fitting, or (2) chose not to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 26 publications
4
83
0
2
Order By: Relevance
“…One study has even reported that the degree of tinnitus impact increases with the degree of hearing loss (Mazurek, Olze, Haupt, & Szczepek, 2010). Further, numerous studies have reported that provision of hearing aids for patients with bothersome tinnitus tends to mitigate their reactions to tinnitus (McNeill, Tavora-Vieira, Alnafjan, Searchfield, & Welch, 2012;Searchfield, Kaur, & Martin, 2010;Shekhawat, Searchfield, & Stinear, 2013). The conclusions from all of these studies are based on the assumption that scores on the tinnitus questionnaires indicate distress due to tinnitus alone.…”
Section: Discussionmentioning
confidence: 99%
“…One study has even reported that the degree of tinnitus impact increases with the degree of hearing loss (Mazurek, Olze, Haupt, & Szczepek, 2010). Further, numerous studies have reported that provision of hearing aids for patients with bothersome tinnitus tends to mitigate their reactions to tinnitus (McNeill, Tavora-Vieira, Alnafjan, Searchfield, & Welch, 2012;Searchfield, Kaur, & Martin, 2010;Shekhawat, Searchfield, & Stinear, 2013). The conclusions from all of these studies are based on the assumption that scores on the tinnitus questionnaires indicate distress due to tinnitus alone.…”
Section: Discussionmentioning
confidence: 99%
“…Several therapeutic approaches-including counseling and behavioral therapy (Andersson & McKenna, 2006;Cima, Andersson, Schmidt, & Henry, 2014;Tyler, Stouffer, & Schum, 1989;Wilson, Henry, Andersson, Hallam, & Lindberg, 1998), the provision of hearing aids (Kochkin & Tyler, 2008;Kochkin, Tyler, & Born, 2011;Searchfield, Kaur, & Martin, 2010;Shekhawat, Searchfield, & Stinear, 2013), and sound therapy devices (Hoare, Searchfield, El Refaie, & Henry, 2014;Tyler, Stocking, Secor, & Slattery, 2014)-can be effective for many people.…”
Section: Discussionmentioning
confidence: 99%
“…Searchfield et al 48 carried out a study to quantify the effectiveness of hearing aids and counselling as a tinnitus treatment option. THQ scores were calculated for pre and post intervention in 58 tinnitus patients receiving counselling with hearing aid and without hearing aid.…”
Section: Parazzini Et Almentioning
confidence: 99%